Filling ability of three bioceramic root-end filling materials: A micro-computed tomography analysis - Toia, Cassia Cestari [UNESP]; Teixeira, Fabricio Batista; Cucco, Carolina; Valera, Marcia Carneiro [UNESP]; Cavalcanti, Bruno Neves (Wiley, 2020)
This study aimed at evaluating the volume of gaps and voids, and the total porosity percentage of three calcium-silicate-based materials in mandibular molars apicoectomy by Micro-CT analysis. Thirty-three mesial roots of extracted human mandibular molars were instrumented and obturated. The apical 3mm of each root was resected and prepared. Root-end cavities were filled with EndoSequence BC Putty (BC); ProRoot MTA (MTA) and Biodentine (BIO). Samples were scanned using a Micro-CT scanner and the tridimensional images reconstructed. Percentage of gaps (VG%) and of voids (VV%) were obtained. Porosity percentage (Po%) was also assessed. Data were analysed using Student’s t-test (P < 0.05). All materials presented gaps and voids. VG% was 2.006 (BC), 1.882 (MTA) and 1.450 (BIO), and VV% was 0.039 (BC), 0.021 (MTA) and 0.024 (BIO) with no statistical difference. Po% were 56.73 (BC), 51.94 (MTA) and 50.45 (BIO), with BC being statistically (P > 0.05) more porous.
Keywords: calcium silicate; endodontic surgery; micro-computed tomography; root-end filling material